Exploring the moderating role of expressive suppression in the relationship between psychopathy and aggression - Maria, Dayla (Nanyang Technological University, 2024)
The link between psychopathy and aggression is well-established and carries significant societal implications. However, there is still a lack of understanding regarding factors that could mitigate this association, as relatively few studies have investigated potential moderators of the psychopathy-aggression relationship. The present study addressed this gap by exploring the role of expressive suppression in the relationship between psychopathy and aggression. It was hypothesized that expressive suppression would moderate the link between psychopathy and reactive, but not proactive aggression. A sample of 123 participants completed self-report measures assessing psychopathy, expressive suppression, and both reactive and proactive aggression. Results showed that psychopathy was significantly positively related to both forms of aggression. Additionally, expressive suppression had a marginally significant moderating effect on the relationship between psychopathy and reactive aggression, after controlling for gender, age, ethnicity, and social adversity. In line with predictions, no such moderating effect was observed for proactive aggression. This study is the first to document that higher levels of expressive suppression may serve as a buffer against the display of certain aggressive behaviors in individuals exhibiting high levels of psychopathic traits. The current findings offer insights into how psychopathy and emotion regulation may interact, showing differential effects on reactive and proactive aggressive tendencies. Moreover, they may potentially inform intervention strategies aimed at reducing reactive aggression in psychopathic individuals.